2015
DOI: 10.1111/apa.12915
|View full text |Cite
|
Sign up to set email alerts
|

Central line bloodstream infections can be reduced in newborn infants using the modified Seldinger technique and care bundles of preventative measures

Abstract: Cost-effective care bundles reduced CLABSI in peripherally inserted central catheters using the modified Seldinger technique, despite the specific insertion skills that were required. The bundles of preventative measures may increase healthcare professionals' awareness of the need to care for central catheters and reduce CLABSI infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
10
0
3
Order By: Relevance
“…Despite excluding the preterm and primarily smaller infants with the highest risk for infection, the CLABSI incidence in our cohort was high compared to the reported incidence in infants >2,500 g. Low gestational age and hygiene are important factors influencing the incidence of CLABSI. Studies have shown that education of medical staff about hygiene, new disinfectant methods, and the use of specific care bundles for catheter placement can reduce the incidence of CLABSI (15, 17, 21, 22). During the last years, we introduced several evidence-based strategies to reduce the incidence of CLABSI in our NICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite excluding the preterm and primarily smaller infants with the highest risk for infection, the CLABSI incidence in our cohort was high compared to the reported incidence in infants >2,500 g. Low gestational age and hygiene are important factors influencing the incidence of CLABSI. Studies have shown that education of medical staff about hygiene, new disinfectant methods, and the use of specific care bundles for catheter placement can reduce the incidence of CLABSI (15, 17, 21, 22). During the last years, we introduced several evidence-based strategies to reduce the incidence of CLABSI in our NICU.…”
Section: Discussionmentioning
confidence: 99%
“…We did not demonstrate a significant difference in CLABSI risk between three catheter types in the NICU. Several studies conducted on how to decrease the incidence of CLABSI have recently shown that proper education of medical staff, the use of specific care bundles and standardization of protocols can prevent CLABSI (15, 21, 22, 33). More extensive follow-up studies are needed to determine the actual incidences of CLABSI in neonates of all gestational ages, which factors genuinely affect the risk of CLABSI and what methods are the most effective for preventing these events.…”
Section: Discussionmentioning
confidence: 99%
“…Such care provides significant reductions in the CLABSI, however, there is no consensus on the use of 70% alcohol and the alcoholic antiseptic solution of chlorhexidine gluconate in neonatology. (23,25,26) In this study, the use of 70% alcohol had a better adhesion by the judges (CVI = 1).…”
Section: Discussionmentioning
confidence: 47%
“…It was identified a lack of studies about this theme related to this specific population, being this, one of the limiting factors of the study. (9,(24)(25)(26)(27) Adherence to the use of bundle has shown significant results in reducing CLABSI in NICU, linked to permanent education practices. (9,26) A meta-analysis aimed at evaluating the efficacy of bundles of CLABSI prevention in neonatal, pediatric and adult Intensive Care Unit, identified that this strategy implementation in different countries presents positive results in costs reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation